Predictors of Long-Term Improvement Following Cognitive Remediation in a Sample With Elevated Depressive Symptoms - Hagen, Bjørn Ingulfsvann; Landrø, Nils Inge; Lau, Bjørn; Koster, Ernst H. W.; Stubberud, Jan (Frontiers in Psychology, 2020)
Objective: Cognitive remediation (CR) techniques (interventions to enhance cognitive functioning) have proven moderately effective in improving cognition and daily functioning in major depressive disorder (MDD). However, baseline predictors of treatment response are lacking. The present study aimed to identify factors influencing long-term CR outcomes in a sample with current or previous, mild or moderate MDD, and with self-reported cognitive deficits. Methods: Forty-two completers of group-based CR (strategy learning or drill-and-practice), were pooled into one sample. Based on change scores from baseline to six-month follow-up, participants were categorized as "improvers" or "nonimprovers" using reliable change index calculations. Measures included a questionnaire of everyday executive functioning and a neuropsychological test of attention. Finally, improvers and nonimprovers were compared in terms of various sociodemographic, psychological, illness-related, and neuropsychological baseline variables. Results: Seventeen participants improved reliably in everyday executive functioning, and 14 demonstrated a reliable improvement in attention. No statistically significant differences emerged between improvers and nonimprovers. Conclusion: No major predictors of CR were identified. Importantly, the current findings are insufficient to guide clinical decision-making. Large-scale studies with a priori hypotheses are needed to make advances in the future.